Changes in chemical composition caused by water–rock interactions across a strike‐slip fault zone: case study of the Atera Fault, Central Japan. Issue 3 (3rd September 2014) - Niwa, M.; Mizuochi, Y.; Tanase, A.
Abstract In some cases, water–rock interactions in fault zones can affect radionuclide migration. Here, we analyzed the chemical compositions of well‐exposed fault rocks from the strike‐slip Atera Fault, Central Japan, in order to understand the variability and behavior of major and selected trace elements. The fault zone has a 1.2‐m‐wide, smectite‐rich fault core and paired damage zones that developed within welded tuff on one side of the core and within granite on the other side. The 30‐cm‐wide, kaolinite‐rich fault gouge is developed in granite cataclasite, and it shows indications of the latest fault activity, while the 1.2‐m‐wide fault core appears to be older. Hydrogen and oxygen isotope ratios in the clay‐rich fault gouges, and carbon and oxygen isotope ratios in carbonates indicate that the two major clay‐rich zones formed in bedrock near the surface, consistent with observed deformation structures. Based on chemical analyses, we identified (1) a slight depletion in SiO2, Na2O, K2O, and light rare earth elements at the edges of the 1.2‐m‐wide fault core, (2) a clear depletion in SiO2, Na2O, K2O, and all rare earth elements except Eu in the 30‐cm‐wide fault gouge, and (3) an increase in CaO, MnO, and heavy rare earth elements across the entire 1.2‐m‐wide fault core. Findings (1) and (2) reflect water–rock interactions in the 1.2‐m‐wide fault core and in the 30‐cm‐wide fault gouge that resulted in the formation of smectite and kaolinite. Finding (3) reflects carbonate precipitation caused by the addition of basalt fragments from a nearby site to the 1.2‐m‐wide fault core during faulting, and subsequent sorption reactions of heavy rare earth elements via processes such as complexation with the carbonates.